Pesantren Ramah Lingkungan: Implementasi Nilai-Nilai Islam dalam Menumbuhkan Kesadaran Ekologis Santri - Fitria Yulianti; Aisa Nada Salsabila; Jenny Safira Aulia Wati; Yeni Arta Metia; Azriel Dani Danuarta; Desi Nurhabibah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the extent to which Islamic secondary schools utilize Islamic values to foster environmental awareness among students. Increasingly complex environmental challenges demand an education that fosters individual awareness and a sense of responsibility toward the environment. In this regard, Islamic secondary schools, as Islamic educational institutions, play a strategic role in instilling Islamic values within the context of environmental conservation. This study employs a qualitative research methodology, utilizing a literature review to examine various relevant sources related to the research topic (such as books, academic journals, and scientific articles). To identify and understand concepts related to Islamic values and ecological awareness, this study employs content analysis. The results indicate that Islamic values such as Tawhid, Amanah, and the concept of humanity as Khalifah play a significant role in enhancing environmental awareness among santri. Therefore, Islamic boarding schools have tremendous potential to serve as agents of change in fostering ecological awareness rooted in Islamic values. This study aims to encourage the development of Islamic education so that it focuses not only on the spiritual dimension but also on ecological sustainability.